The Public Service ontology: a formal model for describing domain-specific semantics. (15th September 2011) - Loutas, Nikolaos; Peristeras, Vassilios; Tarabanis, Konstantinos
The Public Service ontology provides researchers and practitioners with a formal, standardised and unambiguous way for modelling public services. To develop the Public Service ontology, a formal ontology development methodology was followed and a generic Public Administration (PA) service model (Peristeras and Tarabanis, 2008) was used as a blueprint. The ontology played the role of the PA Service ontology in the SemanticGov project. The Public Service ontology has also been used for resolving semantic interoperability problems between different PA information systems and for creating Semantic Web Service with rich PA domain semantics.